Technological Advances and Knowledge-Based Economy on Labor Absorption: Evidence in Indonesia - Sri wahyuny Mustafa; I Ketut Patra; Jusman; Halim Usman; Adya Utami Syukri (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study develops an integrated model to examine the direct and indirect effects of technological advances and the knowledge-based economy on labor absorption through private investment and human capital. Research Objectives: This study aims to analyze the direct and indirect impacts of technology and the knowledge-based economy on labor absorption, with private investment and human capital development as mediating mechanisms, and to formulate an integrated policy framework to improve labor absorption. Research Methods: Three-Stage Least Squares (3SLS) estimation of a three-equation simultaneous system using provincial panel data from 34 Indonesian provinces from 2015 to 2024. Empirical Results: Technological progress and knowledge-based economy development stimulate labor absorption through direct effects and substantial indirect pathways via private investment and human capital accumulation. Private investment signals skill requirements to education systems; human capital attracts further investment through productivity enhancement. Implication: Coordinated multi-sector policies integrating technology adoption, private investment incentives (tax breaks, technology parks), dramatic expansion of vocational education, knowledge-based economy infrastructure, regionally differentiated approaches, and integrated labor market monitoring systems. JEL Classification: J20, J24, O33 How to Cite:Mustafa, S. W., Patra, I. K., Jusman., Usman, H., & Syukri, A. U. (2026). Technological Advances and Knowledge-Based Economy on Labor Absorption: Evidence in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 501-514. https://doi.org/10.15408/sjie.v15i2.47274.